Pengaruh Edukasi Pajak dan Kesadaran Wajib Pajak Terhadap Kepatuhan Wajib Pajak Survei pada UMKM Sektor Kuliner di Kota Bandung - Amelia, Elsa Aisyah; Saepuloh, Cepi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to analyze the effect of tax education and taxpayer awareness on taxpayer compliance in a survey of MSMEs in the culinary sector in Bandung City. The problem of taxpayer compliance is still a challenge for MSME players, even though the government has provided various incentives and facilities in the tax system. This study uses a quantitative approach with a survey method involving 92 respondents from MSME players in the culinary sector in Bandung City. Data were collected through questionnaires and analyzed using multiple linear regression methods. The results of this study reveal that tax education has a positive and significant effect on taxpayer compliance. In other words, the better the taxpayer’s understanding of the tax system, the level of their compliance also tends to increase. In addition, taxpayer awareness also has a positive influence on taxpayer compliance, which indicates that understanding and awareness of the importance of taxes can increase tax compliance. Simultaneously, tax education and taxpayer awareness make a significant contribution to the compliance of MSME taxpayers in the culinary sector in Bandung City. These findings indicate the need to strengthen tax education programs and increase taxpayer awareness through more effective communication strategies.